Kinerja Aparatur Sipil Negara Di Badan Kepegawaian Daerah Kabupaten Jayawijaya - Hilapok, Leonar Son; Areros, William A.; Rares, Joyce J. (AGRI-SOSIOEKONOMI, 2023)
This study aims to find out how, the performance of the state civil apparatus in the Jayawijaya district civil service agency. This research was carried out from February to May 2023. The selection of respondents was done deliberately. The data used are primary data and secondary data. Primary data was collected through interviews, based on questionnaires, to the head of the field and honorary staff respectively. jayawijaya district civil service. So that the total respondents were 6 people. Secondary data was obtained from related agencies, namely through the Jayawijaya Regency Regional Personnel Agency for Human Resources. Secondary data was also obtained through books obtained from local bookstores and the internet via Google Scholar in the form of books, journal articles and theses related to the topic of this research, namely the Performance of State Civil Apparature at the Jayawijaya Civil Service Agency. The results of the study show that the assessment of the performance of state civil servants in the Jayaawijaya Regency Regional Civil Service Agency is not optimal. Because there are still some problems. Based on the quantity indicator, it shows that there are still targets that have not been implemented and work that has exceeded the target, thus increasing the workload. In terms of quality, it was found that many mistakes were made in carrying out the work due to a lack of accuracy and understanding. In terms of time use, it was found that there were still many employees who had not used working hours effectively. Based on the existing problems, there are several suggestions that can be made, namely to increase discipline in working time, the need to improve the quality of work under supervision, provide punishment for employees who violate the provisions of working time and provide rewards for superior performing employees, the need for routine employee development programs , it is necessary to use a finger print for attendance, as well as adding office facilities that are lacking and routine maintenance of facilities and infrastructure.